May Dietary Supplementation Augment Respiratory Burst in Wound-Site Inflammatory Cells? - Das, Amitava (Antioxid Redox Signal, 2018)
Persistent infection contributes to wound chronicity. At the wound site, NADPH oxidase (NOX) activity in immune cells fights infection to enable the healing process. Fermented papaya preparation (FPP) is a carbohydrate-rich nutritional supplement that has demonstrated ability to bolster respiratory burst in experimental rodent systems. In FPP, glucose coexists with fructose and maltose in addition to multiple other sugar alcohols such as inositol. We have previously reported that FPP supplementation augments wound healing in diabetic mice via improvement of respiratory burst activity of wound innate immune cells. In this clinical study (clinicaltrials.gov: NCT02332993), chronic wound patients were orally supplemented with FPP daily. Inducible production of reactive oxygen species was significantly higher in wound-site immune cells from patients supplemented with FPP and on standard of care (SoC) for wound management compared with those patients receiving SoC alone. Wound closure in FPP-supplemented patients showed improvement. Importantly, the consumption of this mixture of carbohydrates, including significant amounts of glucose, did not increase HbA1c. These observations warrant a full-length clinical trial testing the hypothesis that FPP improves wound closure by augmenting NOX activity in immune cells at the wound site. Antioxid. Redox Signal. 28, 401–405.